Comparison of teaching two methods of physical education with grade one pupils - Scott, Robert (My University, 1965)
Five groups of grade one boys and girls (29 pupils in each group) were compared in physical fitness, perceptual motor development and creative ability at the conclusion of a five month program. Each group followed a different program: (a) the informal method four times a week, (b) the formal method four times a week, (c) the informal method twice a week, (d) the formal method twice a week, and (e) no physical education at all. There were no significant differences among the five groups in physical fitness and perceptual motor development at the beginning of the study. The findings of this study would appear to warrant the conclusions that at the five percent level of significance the methods and frequencies followed in this study: (a) do not vary in their effect on perceptual motor development, (b) are equally better than no physical education at all in the development of physical fitness, (c) are less effective 1n the development of creative ability than no physical education at all, and (d) have the same effect on boys as they do on girls.
Keywords: Physical education for children